Gaya Dakwah Digital Gus Kautsar Pada Kajian Irsyadul ‘Ibad Di Youtube Terasgubuk - Abiidah Nafisa Fiqriyah; Luluk Fikri Zuhriyah (Hikmah, 2025)
This study discusses Gus Kautsar's communication style in the routine study of the Irsyadul 'Ibad book delivered through the Terasgubuk YouTube channel on February 7, 2025. In the digital era, social media is currently an important space for delivering Islamic preaching. But not all preachers can adjust or align the way they deliver their preaching with the characteristics of digital audiences who tend to like relevant, reflective and communicative content. Gus Kautsar is one of the preachers who uses a unique and down-to-earth approach, he uses everyday language mixed between Indonesian and Javanese, and delivers the contents of classical books with a light but meaningful style of speech by utilizing the YouTube platform. The research method used is descriptive qualitative with discourse analysis to study the verbal and nonverbal styles used. Gus Kautsar not only delivers material informatively, but also touches on the emotional and spiritual aspects of the audience. His calm demeanor, true stories, and imaginary dialogue techniques make his preaching more alive and he and the audience can be closer. This study clearly proves that the success of digital preaching is greatly influenced by the ability to communicate empathetically, contextually, and humanely. This kind of preaching model is very relevant amidst the dynamics of modern society that thirsts for sincerity and meaning in religious messages.